Pengaruh Faktor-Faktor Fundamental dan Teknikal terhadap Dividend Payout Ratio - Nyi Raden Sella Ayu Ardiyanti (Magister Akuntansi Universitas Pancasila, 2015)
A B S T R A C T This study aims to examine the extent to which the implementation of the cash ratio, debt to equity ratio, return on asstes, earning per share, inflation and interest and dividend payout ratio impact on the results of an empirical study on manufacturing companies in indonesia stock exchange during the period 2010-2014. The sample used in this study as many as 11 companies for 5 years consecutive issued dividend. The analysis technique used in this research is multiple linear regression and hypothesis testing using t-statistic to test the partial regression coefficient and f-statistic to test the feasibility of the research model with 5% level of significance. It also conducted a classic assumption test including normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. Results of the analysis showed that the variable cash ratio, return on asstes, and earning per share, positive and significant impact on the dividend payout ratio, while the variable debt to equity ratio, inflation and interest rate negative and not significant to the dividend payout ratio. A B S T R A K Riset ini bertujuan untuk meneliti sejauh mana implementasi cash ratio, debt to equity ratio, return on asstes, earning per share, Inflasi dan Suku Bunga dan dampaknya pada dividend payout ratio hasil studi empiris pada perusahaan Manufaktur di Bursa Efek Indonesia selama periode 2010-2014. Sampel yang digunakan dalam penelitian ini sebanyak 11 perusahaan yang selama 5 tahun berturut-turut mengeluarkan deviden Teknik analisis yang digunakan dalam penelitian ini adalah regresi linear berganda dan uji hipotesis menggunakan t-statistik untuk menguji koefisien regresi parsial serta f-statistik untuk menguji kelayakan model penelitian dengan level of significance 5%. Selain itu juga dilakukan uji asumsi klasik yang meliputi uji normalitas, uji multikolinieritas, uji heteroskedastisitas dan uji autokorelasi. Hasil analisis menunjukan bahwa variabel cash ratio, return on asstes, dan earning per share, berpengaruh positif dan signifikan terhadap dividend payout ratio, sedangkan variabel debt to equity ratio, Inflasi dan Suku Bunga berpengaruh negatif dan tidak signifikan terhadap dividend payout ratio. JEL Classification: G10, G32